Parameters of spatial comfort in architecture - Alfirević, Đorđe; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2020)
The perception of reality is experienced through the senses, each of which to some extent contributes to the formation of the notion of a sense of comfort. When it comes to the experience of space and spatiality, the most dominant are visual and tactile influences, whose information overpowers the other senses. It is generally accepted in science that there are several basic categories of comfort - visual, thermal, auditory (sound), olfactory (odor) and hygienic comfort. Unlike the previously mentioned terms, spatial comfort is not clearly defined, although it is one of the key terms when talking about human needs and the functionality of space in architecture. In addition to its wide application in practice and the fact that there is still no clear definition of this term in science, its application is understood as the equivalent of the comfort of space. The research analyzes and systematizes the most important parameters whose application provides the opportunity to achieve spatial comfort, which does not mean that spatial comfort will be achieved because it largely depends on the individual perception of space users. In order to clarify the term spatial comfort and formulate its precise definition, the main contribution of the paper is the analysis of parameters through which spatial comfort can be achieved, as well as reviewing the thesis that spatial comfort is a feeling of comfort and satisfaction derived from physical, visual and tactile qualities.